Advancing a holistic systems approach for sustainable cattle development programmes in South Africa: insights from sustainability assessments. Issue 7 (8th August 2020) - Marandure, Tawanda; Bennett, James; Dzama, Kennedy; Makombe, Godswill; Gwiriri, Lovemore; Mapiye, Cletos
ABSTRACT: Efforts to exploit the central roles of cattle to drive agriculture and rural development in low-income countries recorded limited success owing to their narrow focus on modernizing and commercializing low-input cattle farming. Most programs failed to take cognizance of the heterogeneous range of complex relationships between the environmental, economic, social and institutional challenges that limit low-input cattle farming. The current qualitative literature review evaluates the environmental, economic and social sustainability delivery impacts of the leading cattle development programs in the low-input farming sector in South Africa using a holistic systems approach. A mixed method procedure involving stratified sampling was used to allocate local and international-based programs while, purposive sampling was used to select programs with a wider scale of operation. The review then draws on the crosscutting key constraints emerging from the case studies to provide a better grounding for subsequent sustainability sensitive recommendations. Local-based cattle development programs advanced more market-led interventions while, their international-based counterparts had more interventions including, soil and rangeland improvement. The narrow focus by both local and international developmental programs is inadequate to address a wide array of environmental, economic, social, technical and institutional challenges faced by low-input cattle producers in South Africa.